Comparative Study of AI-Based and Direct Instruction on Grinding Machining Learning Outcomes at SMK Turen - Fajar Dwi Kurnia Wijaya; Tuwoso Tuwoso (Jurnal Teknologi Informasi dan Pendidikan, 2026)
This study aimed to determine the effectiveness of Artificial Intelligence (AI)-based learning media on student learning outcomes in the subject of Grinding Machining Engineering at vocational high school level. The research employed a quantitative approach using a pre-experimental design with the One Group Pretest–Posttest Design model. The subjects of this study were 25 students of class X in the Welding Engineering program at SMK Turen. Data collection was conducted using objective multiple-choice tests consisting of 20 items that had passed validity and reliability testing with a Cronbach’s Alpha value of 0.745. Data analysis techniques included descriptive statistics, normality test, homogeneity test, Independent Sample T-Test, and N-Gain analysis using IBM SPSS Statistics version 26. The results showed that the average posttest score in the AI-based learning group was higher than the pretest score. The Independent Sample T-Test showed a significance value of <0.001, indicating a significant difference between AI-based learning and Direct Instruction methods. Furthermore, the N-Gain analysis showed that the AI-based learning group obtained a higher average score (0.615) compared to the Direct Instruction group (0.453), both categorized as moderate improvement. Therefore, AI-based learning media was proven to be more effective in improving student learning outcomes in Grinding Machining Engineering subjects because it provides a more interactive, adaptive, and flexible learning experience.